2010
DOI: 10.1007/s00424-010-0854-9
|View full text |Cite
|
Sign up to set email alerts
|

Epac stimulation induces rapid increases in connexin43 phosphorylation and function without preconditioning effect

Abstract: It has been recently shown that beta-adrenergic receptors are able to activate phospholipase C via the cyclic adenosine monophosphate-binding protein Epac. This new interconnection may participate in isoproterenol (Iso)-induced preconditioning. We evaluated here whether Epac could induce PKCepsilon activation and could play a role in ischemic preconditioning through the phosphorylation of connexin43 (Cx43) and changes in gap junctional intercellular communication (GJIC). In cultured rat neonatal cardiomyocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Consistent with the results reported by others (Duquesnes et al, 2010) who used a similar model of I/R, perfusion of hearts with the Epac agonist CPT did not show a clear protective effect. Nonetheless, we found that perfusion of hearts with the mixture of the specific PKA activator 6‐Bnz and the Epac activator CPT resulted in relatively very high haemodynamic functional recovery (Figure 7A and Table 2), significantly reduced LDH release and infarct size during reperfusion (Figure 7B–C).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the results reported by others (Duquesnes et al, 2010) who used a similar model of I/R, perfusion of hearts with the Epac agonist CPT did not show a clear protective effect. Nonetheless, we found that perfusion of hearts with the mixture of the specific PKA activator 6‐Bnz and the Epac activator CPT resulted in relatively very high haemodynamic functional recovery (Figure 7A and Table 2), significantly reduced LDH release and infarct size during reperfusion (Figure 7B–C).…”
Section: Discussionsupporting
confidence: 92%
“…Cx43 has a high turnover rate with a half-life of ~1-2 h, this condition permits rapid adjustments of cell-cell communication with transcriptional regulation and degradation (18). Modulation of cAMP and its relevant signaling pathway Epac are reported to affect the level of Cx43 and its phosphorylation in the heart (19,20) and endothelial cells (21). However, the molecular nature of β2-AR stimulation and cAMP derivative induced Cx43 expression in astrocytoma cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, some studies reported that EPAC regulates the expression and localization of the main ventricular gap junction protein connexin 43 in a Rap1-and PKCε-dependent manner, thereby influencing the gating function of Gap junctions. 121,122 Considering the importance of connexin 43 in the regulation of electric cell-to-cell coupling and the pathogenesis of ventricular arrhythmias, 123 we can speculate that EPAC contributes to electric remodeling via alterations of gap junction formation.…”
Section: Epac and Cardiac Electric Remodelingmentioning
confidence: 99%